Strategi komunikasi pelajar menengah multi-etnik dalam perbincangan kumpulan / Sivapackiam Maruthai - Sivapackiam, Maruthai (2015)
This study investigated aspects of communication strategies employed by multiethnic Malaysian secondary school students in their oral communication through Bahasa Melayu (BM). The multiethnic students include L1 learners (native speakers) L2 and L3 learners (non-native speakers). Two groups of students with different competency in BM (high and low proficiency) were engaged. The study examined the differences in the use of communication strategies between 28 high and 28 low proficient speakers. The problems occurred during the group discussions among the interlocutors and the communication strategies applied by them to solve the problems were also examined. This study adopted Dornyei’s Taxonomy of Communication Strategies (1995). The communication strategies were divided into three main strategies namely Avoidance Strategies, Achievement Strategies and Stalling or Time Gaining Strategies. The descriptive study incorporated the use of video recordings, observations and unstructured interviews. Data elicited from the video recordings were transcribed and analyzed. The frequency of the type of communication strategies specified by Dornyei’s Taxonomy of Communication Strategies (1995) were also noted. The findings showed that the subjects resorted to 8 out of the 12 types of communication strategies specified by Dornyei’s Taxonomy of Communication Strategies (1995). The findings also indicated that students of high level and low level competence in BM tend to use different kind of communication strategies in their group discussions. The most frequently employed communication strategy used by the high level students were code switching and time gaining strategies whereas the low level the students used non-linguistics strategies, message abandonment and topic avoidance. Students used different kind of communication strategies to overcome the problems faced in their group discussions. Several new communication strategies also emerged and including asking more questions to guide the interlocutors, laughing for no reason and group talking. Finally, it was found that communication strategies should be taught to multiethnic students to enable them to communicate effectively. Language teachers should introduce some useful communication strategies to students to overcome their communication problems.